Prevalence of non-alcoholic fatty liver disease (NAFLD) in patients with type 2 diabetes mellitus and its correlation with coronary artery disease (CAD) - Prabhakar, Anjana; N. R., Ambili; Kartha T. D., Unnikrishnan; B., Renymol (International Journal of Research in Medical Sciences, 2017)
Background: Non-alcoholic fatty liver disease (NAFLD) is a common association of Type 2 diabetes mellitus and diabetes mellitus is a leading risk factor for coronary artery disease (CAD). This study aims at estimating the prevalence of NAFLD by ultrasonography and to correlate NAFLD with CAD in a group of patients with Type 2 DM. Methods: Consecutive patients of Type 2 diabetes fulfilling the inclusion criteria were recruited. Clinical and biochemical parameters were recorded. NAFLD was diagnosed by ultrasonography. Results: The prevalence of NAFLD was 41.2% in the study group (n=114) and was higher in females. Prevalence of NAFLD in the younger age group was significantly higher than that in the older age group. Elevated liver enzymes, elevated HbA1C, duration of diabetes, obesity, acanthosis nigricans and metabolic syndrome were all significantly associated with NAFLD. CAD was significantly higher in the NAFLD subgroup (72.46%) compared to the non-NAFLD subgroup (52.63%) (p=0.001). Using binary logistic regression analysis, it was found that NAFLD is an independent predictor of CAD (p=0.002). Conclusions: NAFLD is extremely common in people with Type 2 diabetes and is associated with a higher prevalence of CAD.NAFLD is an independent risk factor for development of CAD. Thus, identification of NAFLD in diabetics might help in predicting the risk of CAD and to adopt the necessary preventive strategy.